Pengaruh Indikator Makro Ekonomi: Infasi Dan Nilai Tukar Rupiah Terhadap Jumlah Zakat Terkumpul Di Lembaga Amil Zakat Dompet Dhuafa Periode 1997-2013 - Rio Budi Dwitama; Tika Widiastuti (Universitas Airlangga, 2016)
The The purpose of this study was to know the effect of rupiah exchange rate and inflation on the amount of zakah in amil zakah foundation dompet dhuafa period 1997-2013. The approach research that is used is quantitative with multiple linear regression analysis technique. The dependent variable used is the amount of zakah, while the independent variables, rupiah exchange rate and inflation. Determination of the number of samples using non probability sampling with saturated sample method, that all of the population used as sample. Data that being used was secondary data. T test result stated that rupiah exchange rate and inflation has an effect not significant on the amount of zakah. F test result state that simultaneously the rupiah exchange rate and inflation has an effect not significant on the amount of zakah in Amil Zakah Foundation Dompet Dhuafa period 1997-2013.